Methods for Studying Rural Institutions, Networks, and Capacity in the Developing World : Mobilizing Rural Institutions - Agrawal, Arun (World Bank, Washington, DC, 2012)
This note outlines two methods developed by the Mobilizing Rural Institutions study to assess and compare the governance capacities of local institutions and their network relationships in any local context. Local institutions and their institutional networks play a fundamental role in shaping governance and livelihoods outcomes in rural areas, particularly for more marginal and disadvantaged populations. A review of local institutions in nearly 50 cases in 5 countries found that network relationships and linkages among local and external institutions were a key element in promoting governance and livelihoods, as well as more equitable allocation of benefits. Yet despite the consensus that local institutions and their links with other institutions are important in development and conservation efforts, we lack tools to assess and compare networks of local institutions, the strength of their links, and how these contribute to livelihoods outcomes. This note identifies two such tools to help identify leverage points through which new policies can be introduced to maximal effect, and to select appropriate local institutional partners for policy and projects. The first section summarizes two key findings from the report on institutional linkages, governance and livelihoods outcomes. The second section describes the Institutional Network Analysis tool. The third looks at the IAPA (Inclusion, Accountability, Participation and Adaptability) governance index. The final section draws conclusions and identifies recommendations for how the two indexes can be a useful tool for policy and implementation projects that view local institutions as an important partner in development efforts.